Black cumin may be a potential drug for development of carbontetrachloride-induced lung damage in rats - Aslan, Abdullah; Boydak, Didem; Can, Muhammed Ismail; Kuloglu, Tuncay; Baspinar, Serpil (Mattioli 1885, 2016)
The study examines whether Black cumin (Nigella sativa L.) plays a protective role against the damage in the lung by administering carbontetrachloride (CCl4) to rats. 28 male Wistar albino (n=28, 8 weeks old) rats were used in the study. The rats divided into 4 groups according to their live weights. The groups were: (i) Negative Control (NC): Normal water consuming group to which no CCl4 and Black cumin (BC) is administered; (ii) Positive Control (PC): Normal water consuming group to which no CCl4 is administered but BC is administered; (iii) CCl4 Group: Normal water consuming and group to which CCl4 is administered (1.5 ml/kg live weight, ip); (iv) CCl4 + BC group: CCl4 and BC administered group (1.5 ml/kg live weight, ip). Tissue apoptotic index was examined via TUNEL method. MDA (malondialdehyde) determination in lung tissue was made using spectrophotometer. As a results, MDA amount decreased in the CCl4 + BC group (6,33 +/- 1,54 nmol/g) in comparison to CCl4 group (8,66 +/- 1,58 nmol/g) whereas it was observed in the CCl4+BC group (15,35 +/- 0,21%) that the apoptotic index (TUNEL results) decreases in comparison with the CCl4 group (27,48 +/- 0,28%) thus approaching normal values. DNA damage ratio decreased in the CCl4 + BC group in comparison to CCl4 group. These results show that BC plant protects the lung against oxidative damage.
Keywords: Apoptosis; DNA damage; lung; new drug; TUNEL